Endo-parasite fauna of rodents caught in five wet markets in Kuala Lumpur and its potential zoonotic implications. - Sithambaram, Paramasvaran; Abdullah Sani, Rehana; Hassan, Latiffah; Hanjeet, Kaur; Krishnasamy, M.; Jeffery, J.; Louis, Santhana Raj; Sumarni, Mohd Ghazali; Lim, K. H. (Malaysian Society of Parasitology and Tropical Medicine, 2009)

(untitled)
Rodents were collected from five wet markets (Chow Kit, Dato Keramat, Setapak, Jinjang and Kepong) in Kuala Lumpur, Federal Territory between March to April 2006. Ninetyseven rats were trapped using wire traps measuring 29x22x50 cm baited with fruits, coconuts, dried fish or sweet potatoes. A total of 17 different species of parasites were identified from three species of rats out of which 11 (65%) were identified to be zoonotic. The helminths identified from the urban rats were nematodes- Capillaria hepatica, Gongylonema neoplasticum, Heterakis spumosa, Heterakis sp., Masterphorus muris, Nippostrongylus brasiliensis, Physolaptera sp., Pterogodermatis sp., Rictularia tani and Syphacia muris; cestodes- Hymenolepis nana, Hymenolepis diminuta, Hymenolepis sabnema, Hymenolepis sp., Raillietina sp. and Taenia taeniaeformis, and acanthocephalan- Moniliformis moniliformis. The following parasites are of potential medical importance: C. hepatica, G. neoplasticum, R. tani, S. muris, H. diminuta, H. nana, Raillietina sp. and T. taeniaeformis.